When are fiscal deficits inflationary in low-income countries? - Michael F. Bleaney; Atsuyoshi Morozumi; Zakari Mumuni (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2020)
Previous research has found that the relationship between fiscal deficits and inflation is conditional on income levels: deficits tend to be inflationary in developing countries but not in advanced economies. We show that within low-income countries (LICs) the relationship is again conditional: only when relatively poor institutions fail to hold governments accountable to the general public are fiscal deficits inflationary in LICs.
Keywords: E31; H62; O23; 330; Fiscal deficits; Inflation; Government accountability